Sistem Informasi Inventory Menggunakan Progressive Web App Studi Kasus PT. Tifico Fiber Indonesia - Andika Purwara, Yudha (CV. Shofanah Media Berkah, 2023)
Information technology has helped companies and individuals in running their business. The main problem lies in the difficulty of finding spare parts because there are many and can only be done on one PC with Microsoft Office Software (Excel). With so many items in the laboratory, searching for stock cards that match the items to be used is quite time-consuming. This causes a discrepancy between the physical data and the data in the records which can cause losses. Then if there are goods arriving, the goods must be matched with the request data that has been submitted, the recording of receipt of goods has used a web apps-based system but there are still many shortcomings in the application, for example not many users can access the web apps and the application is not user friendly thus hindering work. A lot of time is wasted on accessing these web apps. You have to have another room to access it because it only runs on one PC. PWA technology takes advantage of new technologies that take part from mobile applications and native applications. The main problem is in the process of finding spare parts because there are many and can only be done on one PC with Microsoft Office Software (Excel). In managing the data of sperpat goods it becomes easier and does not make it difficult for users. The PWA system can be opened anywhere. Of course, access is in accordance with the user who enters the PWA system.